2023
DOI: 10.1007/s40520-023-02387-x
|View full text |Cite
|
Sign up to set email alerts
|

What makes older adults feel good?

Abstract: Background and aim To inform health promotion interventions, there is a need for large studies focusing specifically on what makes older adults feel good, from their own perspective. The aim was to explore older adults’ views of what makes them feel good in relation to their different characteristics. Methods A qualitative and quantitative study design was used. Independently living people (n = 1212, mean age 78.85) answered the open-ended question, ‘What … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 33 publications
0
2
0
1
Order By: Relevance
“…Nevertheless, a very low number of respondents monitored the users' heart rate or considered any intensity control system, therefore, despite claiming to perform aerobic exercise, the recommendations were not followed appropriately. Furthermore, gait training was carried out by a low number of participants; despite the fact that previous studies have shown that gait training is one of the activities that is most demanded by older people as it increases their sense of independence [34][35][36][37]. Gait disorders may lead to rapid loss of activities of daily living, and are also related to higher risk of disabilities, falls and mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, a very low number of respondents monitored the users' heart rate or considered any intensity control system, therefore, despite claiming to perform aerobic exercise, the recommendations were not followed appropriately. Furthermore, gait training was carried out by a low number of participants; despite the fact that previous studies have shown that gait training is one of the activities that is most demanded by older people as it increases their sense of independence [34][35][36][37]. Gait disorders may lead to rapid loss of activities of daily living, and are also related to higher risk of disabilities, falls and mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, health status has also been identified as an enabler and barrier to participation in social activities in previous studies ( Townsend et al, 2021 ), and the results of this study further show that the older respondents who participated in activities outside the home showed better perceived health status than the respondents who participated in activities at home or did not participate in any activities. The health status of older individuals may influence participation in social activities and the types of activities in which one can participate ( Nivestam et al, 2023 ), at the same time as activities found meaningful may also promote well-being ( WHO, 2021 ; Nordmyr et al, 2020 ). Supporting participation would therefore be important to ensure that all older persons, regardless of health status, have equal opportunities to engage in desired activities.…”
Section: Discussionmentioning
confidence: 99%
“…Het belang van een verrijkend sociaal leven voor mensen in het algemeen, en ouderen in het bijzonder, is keer op keer aangetoond. Linden Douma heeft dit bijvoorbeeld onderzocht in haar promotieonderzoek (Douma et al, 2017;Nivestam et al, 2023). De sociale dimensie van thuis gaat over de mensen met wie je in huis woont, en die bij je op bezoek komen.…”
Section: De Mensen In De Ruimteunclassified